Tem alguém olhando? uma análise evolucionista sobre o comportamento cooperativo. - Medeiros, Thais Barbosa (2019)
In the present study we tested the influence of social vigilance, cultural orientation, group identification and perception of social norms on cooperative behavior. Indirect Reciprocity Theory states that individuals help others not only when they expect a direct return, but also to build reputation within the group which may bring future benefits. An important prediction of the indirect reciprocity model is that people behave more cooperatively when they believe that their cooperative behavior is observed. In this study, we defined social vigilance as the monitoring of co-specifics in the social environment and the perception of social vigilance as the perception of being monitored in the social environment. In Study 01, the Social Vigilance Perception Scale (EPVS) was constructed and validated. The relations between the perception of social vigilance and the other variables of interest were investigated. Participants were 551 people from the university community that answered an online survey. Exploratory Factor Analysis (EFA) was performed, and a two-dimensional structure was found. It was concluded that EPVS has adequate psychometric properties and that the perception of social vigilance is directly correlated with horizontal individualistic orientation and negatively correlated with income, age, group size and group identification. Study 02 tested, through an experimental study, the effect of cues of social vigilance on the participants' donation behavior. College students were asked to make donations under two conditions, presence or absence of social cues. There were no differences between the values donated by participants in the two conditions. The higher the individualistic orientation, the lower the donated value. Our results suggested that the low perception of social vigilance and the high donated values were related to the strong collectivist orientation of the participants. They also suggest that the individualistic orientation may be related to decreased cooperative behavior.